A 9-Month-Old Boy With "3 Months of Croup" a Devil Inside - Amit Sah MD; Valerie F. Civelli MD; Christina Donath MD; Lulua Mandviwala MD; Arash Heidari MD (SAGE Publishing, 2022)
Coccidioidomycosis (CM) is an endemic fungal disease that is prevalent in the Southwestern United States, Mexico, and Central and South America. The majority of cases are asymptomatic. Symptomatic cases primarily present with pneumonic disease, varying in severity from mild to severe. In a minority, extrapulmonary disease is known to occur. These disseminated cases typically manifest as meningitis, osteomyelitis, synovitis, and integumentary. Coccidioidomycosis has been identified in nearly every part of the body, including the soft tissues and cartilaginous tissues of the oropharynx. Disseminated CM to the larynx specifically in the pediatric populations is rarely documented. This is a case of persistent stridor misdiagnosed as viral croup in a 9-month-old male with protracted disease. Herein, diagnosis and treatment of laryngeal mass found to be CM are defined with a salutatory outcome.